The Evolution of CERN EDMS. Issue 3 (December 2015) - Wardzinska, Aleksandra; Petit, Stephan; Bray, Rachel; Delamare, Christophe; Arza, Griselda Garcia; Krastev, Tsvetelin; Pater, Krzysztof; Suwalska, Anna; Widegren, David
Abstract: Large-scale long-term projects such as the LHC require the ability to store, manage, organize and distribute large amounts of engineering information, covering a wide spectrum of fields. This information is a living material, evolving in time, following specific lifecycles. It has to reach the next generations of engineers so they understand how their predecessors designed, crafted, operated and maintained the most complex machines ever built. This is the role of CERN EDMS. The Engineering and Equipment Data Management Service has served the High Energy Physics Community for over 15 years. It is CERN's official PLM (Product Lifecycle Management), supporting engineering communities in their collaborations inside and outside the laboratory. EDMS is integrated with the CAD (Computer-aided Design) and CMMS (Computerized Maintenance Management) systems used at CERN providing tools for engineers who work in different domains and who are not PLM specialists. Over the years, human collaborations and machines grew in size and complexity. So did EDMS: it is currently home to more than 2 million files and documents, and has over 6 thousand active users. In April 2014 we released a new major version of EDMS, featuring a complete makeover of the web interface, improved responsiveness and enhanced functionality. Following the results of user surveys and building upon feedback received from key users group, we brought what we think is a system that is more attractive and makes it easy to perform complex tasks. In this paper we will describe the main functions and the architecture of EDMS. We will discuss the available integration options, which enable further evolution and automation of engineering data management. We will also present our plans for the future development of EDMS.